2021
DOI: 10.1115/1.4050288
|View full text |Cite
|
Sign up to set email alerts
|

Exploring System of Systems Resilience Versus Affordability Trade-Space Using a Bio-Inspired Metric

Abstract: The objective of this study is to investigate the value of an ecologically inspired architectural metric called the Degree of System Order in the System of Systems (SoS) architecting process. Two highly desirable SoS attributes are the ability to withstand and recover from disruptions (resilience) and affordability. In practice, more resilient SoS architectures are less affordable and it is essential to balance the trade-offs between the two attributes. Ecological research analyzing long-surviving ecosystems (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This shift becomes less prominent with the increasing severity of disruptions and is in keeping with results from preliminary investigations. 80,81 Based on these results it appears that both disruption type and severity are governing factors in deciding the most favorable DoSO range for SoS architectures.…”
Section: Analysis Of the Pareto Optimal Sos Architectures In The Resilience Versus Affordability Tradespacementioning
confidence: 96%
“…This shift becomes less prominent with the increasing severity of disruptions and is in keeping with results from preliminary investigations. 80,81 Based on these results it appears that both disruption type and severity are governing factors in deciding the most favorable DoSO range for SoS architectures.…”
Section: Analysis Of the Pareto Optimal Sos Architectures In The Resilience Versus Affordability Tradespacementioning
confidence: 96%
“…Previously presented in section 4.3.3, ENA is a systems-oriented methodology to analyze interactions among trophic networks. Five stronglydocumented case studies in this review employed ENA [46,81,[85][86][87]. Comprehensive details on ENA methods and metrics are available in [90,97].…”
Section: Enamentioning
confidence: 99%
“…This architectural feature is evaluated using an approach called Ecological Network Analysis (ENA, detailed in Section II-B). Investigation of the resilience vs. affordability trade spaces of (> 38000) notional SoS architectures under various disruption scenarios indicated that ecologically-similar SoS architectures had more desirable resilience and affordability attributes [11], [12]. A recent study found promising correlations between SoS resilience and ENA-based metrics (and other graph-theoretic metrics) [13].…”
Section: Introductionmentioning
confidence: 99%